أثر استراتيجية (K.W.I) وفق التمرينات التوافقية في تطوير أداء مراحل فعالية رمي المطرقة والإنجاز للطلاب - الجبوري، ماهر عبدالله سلمان (الأكاديمية الدولية لتكنولوجيا الرياضة, 2021)
تكمن أهمية البحث بدراسة استراتيجية (K. W. L) وفق التمرينات التوافقية لما لها من دور كبير في نجاح الأداء الحركي لأغلب المهارات الرياضية وذلك من خلال تطبيقها في منهج تعليمي معد من قبل الباحث، ويهدف البحث إلى التعرف على أثر استراتيجية (K. W. L) للتمرينات التوافقية في تطوير أداء مراحل فعالية رمي المطرقة والإنجاز للطلاب. واستخدم في البحث المنهج التجريبي بتصميم المجموعتين المتكافئتين ذات الاختبارين القبلي والبعدي لملائمته لطبيعة المشكلة وأهداف البحث، وطبقت هذه الدراسة على طلاب المرحلة الثانية في كلية التربية البدنية وعلوم الرياضة -جامعة ميسان للعام الدراسي 2018-2019 والبالغ عددهم (64) طالب، (30) طالب مثل عينة البحث الضابطة، (30) طالب مثل عينة البحث التجريبية، وتم استبعاد (4) طلاب لعدم الالتزام. واستخدمت الوسائل والأدوات والاختبارات المناسبة والتي تلائم البحث، وبعد الحصول على النتائج من الاختبارات تم معالجتها إحصائيا من خلال استخدام الحقيبة الإحصائية (SPSS) وخرجت الدراسة باستنتاجات أهمها: أن استخدام الاستراتيجية (K. W. L) وفق التمارين التوافقية في عملية التعلم خصوصا قد أثر وبشكل كبير في نسبة تحسن الأداء الفني لرمي المطرقة. The importance of the research lies in studying the strategy of (K.W.L) according to compatibility exercises because of its great role in the success of the motor performance of most sports skills through its application in an educational curriculum prepared by the researcher. The research aims to identify the effect of the (K.W.L) strategy of harmonic exercises in developing the performance of the effective stages of hammer throwing and achievement for students. The experimental method was used in the research by designing the two equal groups with the two pre and post tests to suit the nature of the problem and the objectives of the research, and this study was applied to students of the second stage of the College of Physical Education and Sports Sciences - University of Maysan for the academic year 2018-2019 of (64) students, (30) students Like the control research sample, (30) students were like the experimental research sample, and (4) students were excluded for non-compliance. Appropriate means, tools, and tests were used that are suitable for the research. After obtaining the results from the tests, they were treated statistically through the use of the statistical bag (SPSS). The study came out with the most important conclusions: The use of the (K.W.L) strategy according to the combinational exercises in the learning process in particular has greatly affected the rate of improvement in the technical performance of the hammer throw.
Keywords: المهارات الرياضية -- طلبة الجامعات -- العمليات التعليمية